Estudios sobre el género Inocybe (Fr.) Fr., en la Península Ibérica e islas Baleares. III. Especies recolectadas en el Valle del Tiétar (Ávila y Toledo) - Esteve-Raventós, Fernando; Villarreal, M.; Heykoop Fung-A-You, Michel (Revista Catalana de Micologia, 2007)
Research on the genus Inocybe (Fr.) Fr., in the Iberian Peninsula andBalearic islands. III. Species collected in the Tiétar Valley (Avila and Toledo, Central Spain). This paper represents a taxonomic contribution to the species of the genus Inocybe (Fr.)Fr. growing in the Tiétar Valley (provinces of Avila and Toledo). Descriptions, microscopical drawings and photographs afforded of I. leptocystis G.F. Atk., 1. Pseudoasterospora Kühner etBoursier and I. subtrivialis sp. nov., not previously recorded for the Iberian Peninsula, are also afforded.